Host-pathogen relationship in retreated tuberculosis with major rifampicin resistance–conferring mutations - Hang, Nguyen Thi Le; Hijikata, Minako; Maeda, Shinji; Thuong, Pham Huu; Huan, Hoang Van; Hoang, Nguyen Phuong; Tam, Do Bang; Anh, Pham Thu; Huyen, Nguyen Thu; Cuong, Vu Cao; Kobayashi, Nobuyuki; Wakabayashi, Keiko; et al. (Frontiers in Microbiology, 2023)
It is assumed that host defense systems eliminating the pathogen and regulating tissue damage make a strong impact on the outcome of tuberculosis (TB) disease and that these processes are affected by rifampicin (RIF) resistance–conferring mutations of Mycobacterium tuberculosis (Mtb). However, the host responses to the pathogen harboring different mutations have not been studied comprehensively in clinical settings. We analyzed clinico-epidemiological factors and blood transcriptomic signatures associated with major rpoB mutations conferring RIF resistance in a cohort study. Demographic data were collected from 295 active pulmonary TB patients with treatment history in Hanoi, Vietnam. When recruited, drug resistance–conferring mutations and lineage-specific variations were identified using whole-genome sequencing of clinical Mtb isolates. Before starting retreatment, total RNA was extracted from the whole blood of HIV negative patients infected with Mtb that carried either the rpoB H445Y or rpoB S450L mutation, and the total RNA was subjected to RNA sequencing after age-gender matching. The individual RNA expression levels in the blood sample set were also measured using real time RT-PCR. Logistic and linear regression models were used to assess possible associations. In our cohort, rpoB S450L and rpoB H445Y were major RIF resistance–conferring mutations (32/87 [36.8%] and 15/87 [17.2%], respectively). H445Y was enriched in the ancient Beijing genotype and was associated with nonsynonymous mutations of Rv1830 that has been reported to regulate antibiotic resilience. H445Y was also more frequently observed in genetically clustered strains and in samples from patients who had received more than one TB treatment episode. According to the RNA sequencing, gene sets involved in the interferon-γ and -α pathways were downregulated in H445Y compared with S450L. The qRT-PCR analysis also confirmed the low expression levels of interferon-inducible genes, including BATF2 and SERPING2, in the H445Y group, particularly in patients with extensive lesions on chest X-ray. Our study results showed that rpoB mutations as well as Mtb sublineage with additional genetic variants may have significant effects on host response. These findings strengthen the rationale for investigation of host-pathogen interactions to develop countermeasures against epidemics of drug-resistant TB.